Aromatase inhibitors can improve the semen quality of aged roosters by up regulating genes related to steroid hormone synthesis - Xuliang Luo; Xuelian Li; Zi Mei; Haobo Zhou; Yan Chen; Haoxing Wang; Ping Qiu; Yanzhang Gong (Poultry Science)
Excessive aromatase can reduce reproductive performance in aged roosters. Aromatase inhibitors (AI) can inhibit the aromatase activity and improve the semen quality of aged roosters. However, relevant molecular mechanism is still unclear. The purpose of this study was to explore the regulatory mechanism of AI letrozole improving semen quality in aged roosters by transcriptomic and proteomic sequencing. In this study, 56-week-old roosters were reared in separate cages on a standard basice diet and oral letrozole 42 days (D) at a daily dose 0.25 mg/kg. Semen quality and serum hormone were measured before (0 D) and after (42 D) letrozole administration. Reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) were detected, respectively. The results indicated that semen volume, sperm motility, sperm density, MMP, testosterone (T) and gonadotropin releasing hormone (GnRH) in letrozole treatment group (LET) were significantly increased than those in control group (CN) (P<0.05); estradiol (E2) and ROS in LET were significantly lower than those in CN (P<0.05). Through transcriptomic and proteomic analysis, we identified 189 differently expressed genes (DEGs) and 64 differentially expressed proteins (DEPs) in the comparison of LET and CN. DEGs and DEPs Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) items are mainly enriched in steroid biosynthetic process, cell differentiation and proliferation, lipid metabolic process, oxidation-reduction process and electron transfer activity. Furthermore, 8 genes including STAR, CYP17A1, NSDHL, SULT1E1, EHF, NRNPA1, PLIN2 and SDHA were identified as key genes for letrozole to regulate semen quality in aged roosters. These results indicate that letrozole can up-regulate the expression of genes related to steroid hormone synthesis, cell differentiation and proliferation, electron transfer activity, and enhance mitochondrial activity, increase testicular weight, and ultimately improve the semen quality of aged roosters.